A programmable multiscale assembly strategy of carbon nanotubes for honeycomb-like networks. (15th October 2022) - Zhang, Jianwei; Cui, Jianlei; Mei, Huanhuan; Wei, Fengqi; He, Xiaoqiao; Mei, Xuesong
Abstract: In order to meet the growing demand for high performance flexible transparent conductive electrode, starting from its hierarchical structure, a programmable multiscale assembly strategy of CNTs for honeycomb-like networks is proposed to hope to improve its performance. The analysis shows that the self-assembly method can realize the CNTs assembly of nonlinear hexagonal structure by constructing the pattern of SAMs. In this paper, a molecular dynamics model at atomic level is established for studying the self-assembly behavior to analyze its mechanism and the influencing factors of the CNTs distribution morphology. Then the process procedures are investigated to prepare multiscale honeycomb-like CNTs networks with size programmable on functionalized SiO2 substrate, while the accuracy of the molecular dynamics model is confirmed. Finally, the conductivity, transparency and transferability of the honeycomb-like CNTs networks are exploited and proved to be suitable for flexible conductive electrode with higher transparency than the CNTs film. This paper paves the way for the study of properties programmable related to the structure of CNTs assembly. Future work towards scalable and stable preparation of honeycomb-like CNTs networks will further validate them as a promising alternative to the traditional CNTs transparent conductive electrode and continue to make efforts in the field of photovoltaic and electrical sensing. Graphical abstract: A programmable multi-scale assembly strategy of CNTs for honeycomb-like networks is investigated in this paper to overcome the challenges that high conductivity and high transparency are usually difficult to achieve at the same time for fabricating flexible transparent conductive electrode. Commercial CNTs are non-covalent modified by surfactants in H2 O environment to separate single or small bundles from powder agglomeration, and SAMs containing the regular honeycomb pattern is obtained by lithography and silane coupling agent for functionalization. When the non-covalent modified CNTs are transferred to the SAMs on SiO2 substrate, self-assembly happened between them to achieve the honeycomb-like networks. The relevant assembly mechanism and assembly process are solved by molecular dynamics simulations and experiments. Through film transfer technology, the conductivity, transparency and transferability of the honeycomb-like CNTs networks are exploited and proved to be suitable for flexible conductive electrode with higher transparency than the CNTs film. Image 1